Review of tribe Syrphini (Dip.: Syrphidae) in Iran - E. Gilasian (نامه انجمن حشره‌شناسی ایران, 2007)
The specimens of the tribe Syrphini, deposited at the Hayk Mirzayans Insect Museum, were examined and 30 species identified, of which one genus and three species are newly recorded from Iran and marked by an asterisk (*). Keys to the genera and species, as well as their distribution in Iran, are provided. The species are as follows:Dasysyrphus albostriatus (Fallen), D. eggeri (Schiner), Dideoides annandalei (Brunetti), Epistrophe eligans (Harris)*, E. euchroma (Kowarz), Episyrphus balteatus (De Geer), Ischiodon aegyptius (Wiedemann), I. scutellaris (Fabricius), Melangyna* cincta (Fallen)*, Meliscaeva cinctella (Zetterstedt), M. auricollis (Meigen), Eupeodes corollae (Fabricius), E. latifasciatus (Macquart), E. lunigar (Meigen), E. nuba (Wiedemann), Scaeva albomaculata (Macquart), S. dignota (Rondani), S. latimaculata (Brunetti), S. pyrastri (Linnaeus), S. rossica Kuznetsov, S. selenitica (Meigen), Sphaerophoria bengalensis Macquart, Sph. rueppelli (Wiedemann), Sph. scripta (Linnaeus), Syrphus ribesii (Linnaeus), S. torvus Osten Sacken, S. vitripennis Meigen, Xanthogramma laetum (Fabricius)*, X. maculipenne Mik and X. pedissequum (Harris).